Understanding the trade-offs between climate change-induced aridity and agricultural water demand in the Souss basin, Morocco - Attar, Oumaima; Brouziyne, Youssef; Bouchaou, Lhoussaine; El Bilali, Ali; Ait Brahim, Yassine; Chehbouni, Abdelghani (Frontiers in Water, 2024)
The concept of integrated water resource management requires an in-depth analysis of water inflows into a river basin. Population growth and the uncertainties associated with climate change are causing increased water stress and droughts, which are impacting agriculture. Hence the need for studies on the impact of climate change on demand-supply interactions in river basins. In this study, a generic decision support system, ModSim, was used; for the first time in the region; to examine the agricultural water usage and demands over Souss basin in Morocco. ModSim was calibrated over the period from 1990 to 2019 using recorded data about physical processes and hydraulic infrastructures features and management. The simulations succeeded in replicating different deficit episodes at the various irrigated perimeters. During the simulated period from 2012 to 2019, it was observed that the water supplies for the different dams in the basin experienced a decline ranging from 38% to 89%. As a result, the average total unmet demand for surface water from reservoirs in irrigated areas reached 201 Mm3 between 1990-2019 and the monthly average demand increases by 55% in the dry season, compared to the demands in the rest of the year. The significant amount of unmet demand across all sites suggests that demands are satisfied by the withdrawal of water from groundwater resources. The adopted approach has proven to be a useful decision support tool to understand water resources planning challenges. Water managers require such reliable tools to represent the basin’s water trade-offs. Thus, additional investigation to improve the representation of groundwater/surface water interaction approaches is required to enhance the evaluation of the consequences of different uses, especially in arid and semi-arid regions with significant water stress such as Souss. A conceptual framework as well as a detailed discussion have been produced in order to guide efficient water management and governance.